REVITALISASI JURNALISME KOMUNITAS - Jusuf, Arfan (Komodifikasi, 2018)
Modernization of information and communication technology at least has a few significant implication for citizen journalism activities. Hence, citizen journalism can make a revitalization to positionate its excistance democracy pillar on the online world. Citizen journalism on the other side, has important roles to supply and accommodate the public aspiration too to make democracy could be affirmated when the state can make accommodative and transparent communication with the society (citizen).